Abdel-Ghany A EI-Helby Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Al-Azhar University, Nasr City, Cairo, Egypt - Helby, Abdel-Ghany A EI- (Biological Sciences - PJSIR, 2001)
The potassium salts of N-substituted anthranilic acid (I) were allowed to react with Nt-chloroacetylsulfonamides (II), to give substitutedaminosulfamoylphenylaminocarbonylmethyl,N-substitutedanthranilicacid esters (III). The structure of the produced ester (III) were confirmed by microanalytical and spectral data. Preliminary pharmacological testing of the new esters showed that, some derivatives were found to possess marked antipyretic, analgesic and antispasmodic activities compared with paracetamol and atropine as reference drugs.